2015
DOI: 10.2174/1389202916666151014222603
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the Genes Altered in Bladder Neoplasms in Pediatric and Teen Patients Allows Identifying Two Main Classes of Biological Processes Involved and New Potential Therapeutic Targets

Abstract: Research on bladder neoplasms in pediatric and teen patients (BNPTP) has described 21 genes, which are variously involved in this disease and are mostly responsible for deregulated cell proliferation. However, due to the limited number of publications on this subject, it is still unclear what type of relationships there are among these genes and which are the chances that, while having different molecular functions, they i) act as downstream effector genes of well-known pro- or anti- proliferative stimuli and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 218 publications
(231 reference statements)
0
2
0
Order By: Relevance
“…According to a novel form of network-based gene enrichment, Lena et al proposed a more effective method for detecting BPs associated diseases [10], which may help us to better understand the mechanism of different diseases if we can determine the BPs of diseases. Another study has found that altered genes in bladder neoplasm patients were mainly enriched for two classes of BP through GO analysis, which suggests that these BPs may participate in the onset of this disease or worsen the observed phenotype [11]. In addition, Wirapati et al discovered that the GO-BPs with high ‘coexpression’ genes could help to reveal the common thread connecting molecular subtyping and several prognostic signatures of breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a novel form of network-based gene enrichment, Lena et al proposed a more effective method for detecting BPs associated diseases [10], which may help us to better understand the mechanism of different diseases if we can determine the BPs of diseases. Another study has found that altered genes in bladder neoplasm patients were mainly enriched for two classes of BP through GO analysis, which suggests that these BPs may participate in the onset of this disease or worsen the observed phenotype [11]. In addition, Wirapati et al discovered that the GO-BPs with high ‘coexpression’ genes could help to reveal the common thread connecting molecular subtyping and several prognostic signatures of breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed a method for drug repositioning based on disease-associated GO-BP [17]. Meanwhile, Porrelloa and Piergentilib identified new potential therapeutic targets for bladder neoplasm by analyzing BP in which altered genes were enriched [11], which provided strong support for screening new drugs based on GO-BP. However, no studies have focused on the association between drugs and GO-BPs in MG.…”
Section: Introductionmentioning
confidence: 99%